2020
DOI: 10.1093/eurheartj/ehaa640
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using deep learning to detect coronary artery disease based on facial photo

Abstract: Aims Facial features were associated with increased risk of coronary artery disease (CAD). We developed and validated a deep learning algorithm for detecting CAD based on facial photos. Methods and results We conducted a multicentre cross-sectional study of patients undergoing coronary angiography or computed tomography angiography at nine Chinese sites to train and validate a deep convolutional neural network for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 24 publications
0
48
0
2
Order By: Relevance
“…However, image screening is not indicated in asymptomatic patients and patients with nonspecific symptoms, especially those who are not in high prevalence regions [ 44 , 78 ]. It would be more challenging to identify and quarantine them, as well as control further spread by undetected infected and nonspecific symptomatic individuals [79] . Recent research reported applications of a facial features-based AI model in coronary artery disease detection [80] .…”
Section: Further Requirements For Ai During the Covid-19 Pandemicmentioning
confidence: 99%
“…However, image screening is not indicated in asymptomatic patients and patients with nonspecific symptoms, especially those who are not in high prevalence regions [ 44 , 78 ]. It would be more challenging to identify and quarantine them, as well as control further spread by undetected infected and nonspecific symptomatic individuals [79] . Recent research reported applications of a facial features-based AI model in coronary artery disease detection [80] .…”
Section: Further Requirements For Ai During the Covid-19 Pandemicmentioning
confidence: 99%
“…Действительно, в знаковом исследовании, только что опубликованном в EHJ [44], китайская группа ученых разработала глубокую СНС, которая обнаруживает ИБС (со стенозом >50%, документированным ангиографией), анализируя фотографии лица пациента (рис. 4).…”
Section: ии и новая коронавирусная инфекцияunclassified
“…Artificial intelligence can already issue reports with a high correlation with the impression of radiologists for various imaging exams, streamlining the process 10 . Recently, artificial intelligence with "deep learning" was able to identify patients with coronary artery disease with high accuracy through facial recognition 11 . The Emergency Unit of the future will have an increase in the pre-test probabilities with this instantaneous resource.…”
Section: Editorialmentioning
confidence: 99%